2020
DOI: 10.3758/s13415-020-00810-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural indices of orienting, discrimination, and conflict monitoring after contextual fear and safety learning

Abstract: Investigations of fear conditioning have recently begun to evaluate contextual factors that affect attention-related processes. However, much of the extant literature does not evaluate how contextual fear learning influences neural indicators of attentional processes during goal-directed activity. The current study evaluated how early attention for task-relevant stimuli and conflict monitoring were affected when presented within task-irrelevant safety and threat contexts after fear learning. Participants (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Associations with worry, rumination, and depressive symptoms were examined. Furthermore, theoretical models indicate that attentional control disruptions are a key feature of pathological worry (Hirsch & Mathews, 2012) and empirical work has demonstrated that attention control supports adaptive error-monitoring (White et al, 2018) and attentional deployment (White et al, 2020; Taylor, Grant, Frosio, et al, 2020; Taylor, Grant, Kraft, et al, 2020) in the context of worry. Study 3 also included forced entry regression analyses where all subscales identified during factor analysis predict future depressive and worry symptoms, separately.…”
mentioning
confidence: 99%
“…Associations with worry, rumination, and depressive symptoms were examined. Furthermore, theoretical models indicate that attentional control disruptions are a key feature of pathological worry (Hirsch & Mathews, 2012) and empirical work has demonstrated that attention control supports adaptive error-monitoring (White et al, 2018) and attentional deployment (White et al, 2020; Taylor, Grant, Frosio, et al, 2020; Taylor, Grant, Kraft, et al, 2020) in the context of worry. Study 3 also included forced entry regression analyses where all subscales identified during factor analysis predict future depressive and worry symptoms, separately.…”
mentioning
confidence: 99%
“…The valence dimension was reported to differentiate the amplitudes within the P200 component, namely positive stimuli evoke more positive potentials than the negative ones [ 69 ]. The context of safety, which could be connected to the positive valence of emotions and relatively low arousal, was also reported to evoke more positive P200 amplitudes in the flanker task than in the threat context, which could be interpreted as negative and highly arousing [ 70 ]. The stimuli presenting people from the same race as the participant, which could be interpreted as more positive and more significant stimuli, were also reported to evoke more positive amplitudes than the stimuli presenting people of different races [ 71 ].…”
Section: Introductionmentioning
confidence: 99%